In vitro Propagation of Cymbidium aloifolium Sw. Through Shoot-Tip Culture - Kaur Saranjeet (Journal of Horticultural Research)
The research aimed to investigate the regenerative capacity of Cymbidium aloifolium shoot tips obtained in vitro. Shoot-tip explants (< 1–2 mm) of C. aloifolium were cultured on Mitra medium supplemented with cytokinins and auxins individually and in combinations. The regenerative response, proliferation of regenerants, and subsequent plantlet development were evaluated. Explants (< 1 mm) remained resistant to regeneration, whereas those 1–2 mm responded to the chemical stimulus. Auxins were highly beneficial in initiating the regenerative response and early plantlet development. Protocorms multiplied best on medium containing sucrose at a concentration of 15 g·L-1.